2002
DOI: 10.1016/s0370-1573(02)00301-0
|View full text |Cite
|
Sign up to set email alerts
|

The calculus of many instantons

Abstract: We describe the modern formalism, ideas and applications of the instanton calculus for gauge theories with, and without, supersymmetry. Particular emphasis is put on developing a formalism that can deal with any number of instantons. This necessitates a thorough review of the ADHM construction of instantons with arbitrary charge and an in-depth analysis of the resulting moduli space of solutions. We review the construction of the ADHM moduli space as a hyper-Kähler quotient. We show how the functional integral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
619
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(631 citation statements)
references
References 209 publications
(637 reference statements)
12
619
0
Order By: Relevance
“…Of course, the ADS superpotential for this case can also be constructed along the same lines as section 3.2, see e.g. [18]. In fact, this derivation is somewhat simpler than the one for the SU(N) gauge group since there are no ADHM constraints at all in the one instanton case.…”
Section: Instanton Sectormentioning
confidence: 98%
See 3 more Smart Citations
“…Of course, the ADS superpotential for this case can also be constructed along the same lines as section 3.2, see e.g. [18]. In fact, this derivation is somewhat simpler than the one for the SU(N) gauge group since there are no ADHM constraints at all in the one instanton case.…”
Section: Instanton Sectormentioning
confidence: 98%
“…The above action is exactly the same which appears in the ADHM construction as reviewed in [18]. Gauge theory nodes are represented by round circles, instanton nodes by squares.…”
Section: Recovery Of the Ads Superpotentialmentioning
confidence: 99%
See 2 more Smart Citations
“…In section 2.1 we found that the Lunin-Maldacena expression for τ in Eq. (2.6) did not transform covariantly under the 7 Where T is a T-duality and s is a shift. 8 In particular, the dilaton-axion field τ in the Lunin-Maldacena background does not agree with the SYM instanton expression (4.10) unless β is small.…”
Section: Dilaton-axion Pairmentioning
confidence: 98%